The role of the institutions in EU energy policy - Purón Herreros de Tejada, Alejandra (Razón y fe, 2019)
The Framework Strategy for an Energy Union has transformed some traditionally national competences into shared competences with the European institutions. The creation of a common energy market has required a dual system of regulation, in which technical institutions have acquired great importance in drafting legislation and implementing projects. This article deals with the role of the different actors in electricity interconnection projects between Spain and France, and their attitude in favour or to the detriment of EU objectives, depending on the national and economic interests in question.